From zero to thrive: A model of cross‐system and cross‐sector relational health to promote early childhood development across the child‐serving ecosystem. Issue 4 (31st May 2022) - Miller, Alison L.; Stein, Sara F.; Sokol, Rebeccah; Varisco, Rachel; Trout, Phoebe; Julian, Megan M.; Ribaudo, Julie; Kay, Joshua; Pilkauskas, Natasha V.; Gardner‐Neblett, Nicole; Herrenkohl, Todd I.; Zivin, Kara; et al.
Abstract: Early relational health between caregivers and children is foundational for child health and well‐being. Children and caregivers are also embedded within multiple systems and sectors, or a "child‐serving ecosystem", that shapes child development. Although the COVID‐19 pandemic has made this embeddedness abundantly clear, systems remain siloed and lack coordination. Fostering relational health amongst layers of this ecosystem may be a way to systematically support young children and families who are facing adversity. We integrate theory, examples, and empirical findings to develop a conceptual model informed by infant mental health and public health frameworks that illustrates how relational health across the child‐serving ecosystem may promote child health and well‐being at a population level. Our model articulates what relational health looks like across levels of this ecosystem from primary caregiver‐child relationships, to secondary relationships between caregivers and child‐serving systems, to tertiary relationships among systems that shape child outcomes directly and indirectly. We posit that positive relational health across levels is critical for promoting child health and well‐being broadly. We provide examples of evidence‐based approaches that address primary, secondary, and tertiary relational health, and suggest ways to promote relational health through cross‐sector training and psychoeducation in the science of early development. This model conceptualizes relational health across the child‐serving ecosystem and can serve as a template for promoting child health and well‐being in the context of adversity. Resumen: La salud de la temprana relación entre quienes prestan cuidado y los niños es fundamental para la salud y el bienestar del niño. Los niños y quienes les cuidan forman parte de múltiples sistemas y sectores, o un "ecosistema de servicio al niño, " que moldea el desarrollo del niño. Aunque la pandemia del COVID‐19 ha demostrado abundante y claramente esta pertenencia, los sistemas permanecen aislados y les hace falta coordinación. Fomentar la salud de la relación entre las capas del ecosistema pudiera ser una manera de apoyar sistemáticamente a los niños pequeños y familias que se enfrentan con situaciones adversas. Presentamos un modelo conceptual con base en marcos de trabajo de la salud mental infantil y la salud pública que ilustra cómo la salud de la relación a lo largo del ecosistema de servicio al niño pudiera promover el desarrollo del niño al nivel de grupo de población. Nuestro modelo articula cómo aparece la salud de la relación a lo largo de los niveles del ecosistema desde las relaciones entre quien presta el cuidado primario y el niño, hasta las relaciones secundarias entre quienes prestan el cuidado y loa sistemas de servicio al niño, y las relaciones terciarias entre sistemas que amoldan directa e indirectamente los resultados en el niño. Una positiva salud de la relación a través de todos los niveles es esencial para promover la salud y el bienestar del niño de manera amplia. Describimos ejemplos específicos de salud de la relación primaria, secundaria y terciaria, y sugerimos maneras de promover la salud de la relación a través del entrenamiento intersectorial y la educación sicológica dentro de la ciencia del desarrollo temprano. Este modelo conceptualiza la salud de la relación a lo largo del ecosistema de servicio al niño y puede ser un esquema patrón para promover el desarrollo del niño dentro del contexto de situaciones adversas. Résumé: La Santé Relationnelle Précoce entre les personnes prenant soin des enfants et les enfants est fondamentale pour la santé de l'enfant et son bien‐être. Les enfants et les personnes prenant soin d'eux sont encastrés dans de multiples systèmes et des secteurs, ou un « écosystème » servant l'enfant qui forme le développement de l'enfant. Bien que la pandémie du Covid19 ait rendu cet encastrement très clair, les systèmes demeurent compartimentés et manquent de coordination. Cultiver la santé relationnelle au sein des couches de l'écosystème pourrait s'avérer être une manière de soutenir des jeunes enfants et les familles faisant face aux obstacles. Nous présentons un modèle conceptuel informé par les structures de la santé mentale du nourrisson et de la santé publique qui illustre la manière dont la santé relationnelle au travers de l'écosystème servant les enfants peut promouvoir le développement de l'enfant au niveau de la population. Notre modèle articule ce à quoi la santé relationnelle ressemble au travers des niveaux de l'écosystème, des relations entre la personne principale qui s'occupe de l'enfant et l'enfant aux relations secondaires entre les personnes prenant soin de l'enfant et les systèmes servant l'enfant, jusqu'aux relations tertiaires entres les systèmes qui donnent forme aux résultats directement et indirectement. Une santé relationnelle positive au travers de tous les niveaux est critique pour la promotion de la santé de l'enfant et de son bien‐être en général. Nous décrivons des exemples spécifiques de santé relationnelle primaire, secondaire et tertiaire, et suggérons des manières de promouvoir la santé relationnelle au travers de la formation entre secteurs et de la psychoéducation dans la science du développement précoce. Ce modèle conceptualise la santé relationnelle au travers de l'écosystème servant l'enfant et peut servir de modèle pour la promotion du développement de l'enfant dans le contexte de l'adversité. Zusammenfassung: Von Null zum Erfolg: Ein Modell der system‐ und sektorübergreifenden relationalen Gesundheit zur Förderung der frühkindlichen Entwicklung im gesamten Ökosystem der Kinderbetreuung/‐erziehung Die frühe relationale Gesundheit zwischen Bezugspersonen und Kindern ist von grundlegender Bedeutung für die Gesundheit und das Wohlbefinden von Kindern. Kinder und Bezugspersonen sind in mehrere Systeme und Sektoren integriert, die die kindliche Entwicklung prägen, sozusagen in ein "Ökosystem der Kinderbetreuung/‐erziehung". Obwohl die COVID‐19‐Pandemie gezeigt hat, wie wichtig diese Integration ist, sind die Systeme nach wie vor isoliert und unkoordiniert. Eine Förderung der relationalen Gesundheit über die verschiedenen Ebenen des Ökosystems hinweg könnte ein Weg sein, um junge Kinder und Familien, die mit Widrigkeiten konfrontiert sind, systematisch zu unterstützen. Wir stellen ein konzeptionelles Modell vor, das sich auf das psychische Gesundheitswesen für Kinder und das öffentliche Gesundheitswesen stützt. Das Modell veranschaulicht, wie relationale Gesundheit im gesamten Ökosystem der Kinderbetreuung/‐erziehung die kindliche Entwicklung auf Bevölkerungsebene fördern kann. Unser Modell beschreibt, wie relationale Gesundheit auf allen Ebenen des Ökosystems aussieht, von der primären Beziehung zwischen Bezugsperson und Kind über die sekundären Beziehungen zwischen der Bezugsperson und den Kinderbetreuungs /‐erziehungssystemen bis hin zu den tertiären Beziehungen zwischen den Systemen, die direkte und indirekte Einflüsse auf Kinder haben. Positive relationale Gesundheit auf allen Ebenen ist entscheidend für die Gesundheitsförderung und das Wohlbefinden von Kindern im Allgemeinen. Wir beschreiben spezifische Beispiele für primäre, sekundäre und tertiäre relationale Gesundheit. Außerdem schlagen wir Möglichkeiten zur Förderung der relationalen Gesundheit durch sektorübergreifende Ausbildung und Psychoedukation im wissenschaftlichen Feld der frühkindlichen Entwicklung vor. Dieses Modell konzeptualisiert relationale Gesundheit im gesamten Ökosystem der Kinderbetreuung/‐erziehung und kann als Vorlage für die Förderung kindlicher Entwicklung im Kontext von Widrigkeiten dienen. 抄録: 0からの成功:子ども支援エコシステム全体で幼児期の発達を促進するための、 システム間共通で分野横断的な関係性における健康のモデル 養育者と子どもの間の早期の関係性における健康は、子どもの健康と幸福の土台となる。子どもと養育者は、子どもの発達を形作る複数のシステムや活動分野、または"子ども支援エコシステム"の中に組み込まれている。COVID‐19のパンデミックにより、この組み込み性は明らかになったが、システムは依然として地下に埋め込まれているような状態で (サイロ化され) 、調整が取れていない。エコシステムの層の間で関係性における健康を育むことは、逆境に直面している幼い子どもや家族を体系的に支援する方法かもしれない。私たちは、子ども支援エコシステム全体の関係性における健康が、集団レベルでの子どもの発達をどのように促進するかを提示した乳幼児のメンタルヘルスと公衆衛生の枠組みに基づいた概念モデルを示す。私たちのモデルは、一次的な養育者‐子どもの関係性から、養育者と子ども支援システムとの二次的な関係、そして子どもの結果を直接・間接的に形成するシステム間の三次的な関係に至るまで、エコシステムのレベルを超えた関係性における健康がどのようなものかを明確にしている。あらゆるレベルでの肯定的な関係性における健康は子どもの健康と幸福を広く促進するために重要である。一次、二次、三次の関係性における健康の具体的な例を説明し、早期発達の科学における分野横断的なトレーニングと心理教育を通じてそれを促進する方法を提案します。このモデルは、子ども支援エコシステム全体の関係性における健康を概念化したもので、逆境の中で子どもの発達を促進するためのモデルとなり得る。 摘要: 看护者和儿童之间的早期关系健康是儿童健康与福祉的基础。儿童和看护者被嵌入到塑造儿童发展的多个系统和部门, 或"儿童服务生态系统"中。尽管COVID‐19大流行使这种嵌入性非常清晰, 但系统间仍然孤立且缺乏协调。促进生态系统各层之间的关系健康, 可能是系统地支持面临逆境的幼儿和家庭的一种方式。我们提出了一个由婴儿心理健康和公共卫生框架提供信息的概念模型, 该模型说明了整个"儿童服务生态系统"中的关系健康如何在大众层面促进儿童发展。我们的模型阐明了各生态系统层面上的关系健康状况, 从主要的看护者‐儿童关系, 到看护者和儿童服务系统之间的二级关系, 再到直接或间接影响儿童发展的各系统之间的三级关系。各个层面上积极的关系健康对于广泛促进儿童健康和福祉至关重要。我们描述了初级、二级和三级关系健康的具体例子, 并提出了通过早期发展科学中的跨部门培训和心理教育来促进关系健康的方法。该模型将整个"儿童服务生态系统"中的关系健康概念化, 可以作为在逆境中促进儿童发展的模板。 ملخص: من الصفر إلى النمو: نموذج للصحة العلائقية عبر الأنظمة وعبر القطاعات لتعزيز نمو الطفولة المبكرة عبر النظام البيئي لخدمة الطفل تعد صحة العلاقات المبكرة بين مقدمي الرعاية والأطفال أمرًا أساسيًا لصحة الطفل ورفاهيته. ويتعامل الأطفال ومقدمي الرعاية في أنظمة وقطاعات متعددة ، أو "نظام بيئي يخدم الأطفال" ، والذي يشكل تطور الطفل. على الرغم من أن جائحة كوفيد ‐19 قد جعل هذا التضمين واضحًا تمامًا ، إلا أن هذه الأنظمة مازالت معزولة وتفتقر إلى التنسيق. قد يكون تعزيز الصحة العلائقية بين مستويات النظام البيئي وسيلة للدعم المنهجي للأطفال الصغار والأسر الذين يواجهون الصعوبات. نقدم نموذجًا مفاهيميًا مستمداً من أطر الصحة النفسية والصحة العامة للرضع والذي يوضح كيف أن الصحة العلائقية عبر النظام البيئي الذي يخدم الأطفال قد تعزز نمو الطفل على المستوى المجتمعي. يوضح نموذجنا كيف تبدو الصحة العلائقية عبر مستويات النظام البيئي من العلاقات الأولية بين مقدم الرعاية والطفل ، إلى العلاقات الثانوية بين مقدمي الرعاية وأنظمة خدمة الأطفال ، إلى العلاقات من الدرجة الثالثة بين الأنظمة التي تشكل نتائج الأطفال بشكل مباشر وغير مباشر. تعد صحة العلاقات الإيجابية على جميع المستويات أمرًا بالغ الأهمية لتعزيز صحة الطفل ورفاهيته على نطاق واسع. تصف هذه الدراسة أمثلة محددة للصحة العلائقية الأولية والثانوية والدرجة الثالثة ، وتقدم اقتراحات لوسائل لتعزيز الصحة العلائقية من خلال التدريب عبر القطاعات والتعليم النفسي في علم النمو المبكر. يصور هذا النموذج مفهوم الصحة العلائقية عبر النظام البيئي الذي يخدم الأطفال ويمكن أن يكون نموذجًا لتعزيز نمو الطفل في سياق المواقف الصعبة.